Examining the Correlation Between Out-On-Pass Privileges and Post-Discharge Urine Drug Test Outcomes in an Addiction Rehabilitation Center in Qatar - Faycal Walid Ikhlef (22827494) (2025)
Background Substance use disorder (SUD) is a chronic and recurrent condition posing a significant health burden. The integration of out-on-pass (OOP) or day leave privileges during inpatient rehabilitation has been theorized to support recovery by enhancing social reintegration and preparing patients for discharge. However, evidence on the impact of inpatient OOP on post-discharge relapse rates is scant. This study investigates the effect of OOP during inpatient treatment and relapse outcomes. Methods A retrospective cohort design was used to analyze data from 72 patients discharged from the Umm Salal Treatment and Rehabilitation Center in 2023, focusing on OOP during rehabilitation and urine drug test results during aftercare. Key variables included OOP frequency, comorbid personality disorders, forensic history, and relapse indicators. Statistical evaluation utilized logistic regression, chi-squared tests (Fisher’s exact test where appropriate), and survival analysis to identify predictors of relapse, adjusted for potential confounders. Results Of the participants, 28 (38.9%) were granted OOP during inpatient treatment, while 44 (61.1%) were not. Relapse, defined by a positive urine drug screening post-discharge, occurred in 29 patients (40.3%). The median time-to-relapse was 28 days, with a longer duration observed among those granted OOP. Specifically, during the 26-week study period, 25% of patients with OOP relapsed compared to 50% of those without OOP (statistically significant difference; P = .04892). Survival analysis revealed that time-to-relapse was substantially longer for patients who were granted OOP compared to those who were not ( P = .034). Furthermore, the granting of OOP during inpatient treatment of SUD was associated with a 73.2% reduction in relapse hazards ratio ( P = .00876). Conclusion This study highlights the potential of OOP as a therapeutic strategy and tool to support sustained recovery in patients with SUD. While relapse remains a significant challenge, OOP may contribute to extended abstinence periods and reduced relapse rates. Other Information Published in: Substance Use & Addiction Journal License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/29767342251357089